2014
DOI: 10.1002/2014gb004842
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of anthropogenic phosphorus to agricultural soil fertility and food production

Abstract: Agricultural intensification over the last few decades has been accompanied by the extensive use of anthropogenic phosphorus (P) derived from mined phosphate rock. Given the increasing scarcity of P resources, accurate estimates of the reliance of agriculture on anthropogenic P are required. Here we propose a modeling approach for assessing the contribution of anthropogenic P to agricultural soil fertility and food production. We performed computations at country level, and France was chosen as a typical weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 42 publications
3
42
0
1
Order By: Relevance
“…A small fraction (8 %) of P from mined phosphate rock is used to produce animal feed additives. Apart from fertilizer and animal feed additives, the rest of the mined P is used to produce detergents and other products directly consumed by humans (Ringeval et al, 2014). Atmospheric Figure 1.…”
Section: P Inputsmentioning
confidence: 99%
See 1 more Smart Citation
“…A small fraction (8 %) of P from mined phosphate rock is used to produce animal feed additives. Apart from fertilizer and animal feed additives, the rest of the mined P is used to produce detergents and other products directly consumed by humans (Ringeval et al, 2014). Atmospheric Figure 1.…”
Section: P Inputsmentioning
confidence: 99%
“…the budget); P > 0 indicates net P accumulation in the soil, P < 0 indicates a net deficit, and P = 0 represents no net change. P calculated in this manner does not reflect the legacy effects from previous management and fertilization practices (Ringeval et al, 2014), but it is a useful metric to identify regions with a P surplus or deficit at any point in time and to compare countries. Annual soil P values were calculated as the differences between annual inputs and outputs.…”
Section: Annual P Budgets Of Cropland and Pasture Soilsmentioning
confidence: 99%
“…6 Tg. Ringeval et al (2014) estimated that over 80 % of the total P in French soils is associated with past P inputs (equivalent to ca. 65 Tg).…”
Section: Introductionmentioning
confidence: 99%
“…As is well known, the growing consumption of inorganic phosphorus (P) fertilizers has contributed to major increases in crop yields since the 1950s (MacDonald et al 2011). For example, Ringeval et al (2014) found that the contribution of anthropogenic P to food production in France was as high as 84 %. In the United States, crop production would decline at least around 50 % over time without N, P, and K commercial fertilizer (Ringeval et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ringeval et al (2014) found that the contribution of anthropogenic P to food production in France was as high as 84 %. In the United States, crop production would decline at least around 50 % over time without N, P, and K commercial fertilizer (Ringeval et al 2014). P mined from phosphate rock is a finite fossil resource with highly concentrated deposits -more so than that for oil reserves (Vaccari 2009).…”
Section: Introductionmentioning
confidence: 99%